Addressing cultural differences resulting from immigration: a comparison between French and Swedish public policies - Coulet, Cyril (Sens public)

(untitled) (Département des littératures de langue française, 2010)
Most French scholars tend to oppose the swedish model of immigration to the french one as they are thought to handle the otherness of the other in opposite ways. These two distinct models are thought to call forth the well established distinction between the traditional communitarian approach to otherness and the individual universal one. The French model is therefore seen as stressing the right of the individual irrespective of the right of the groups whereas the Swedish model is depicted as promoting the rights of communities before those of individuals. This distinction is appealing at first sight since it provides an insight into the global frame of reference for Swedish and French policies handling the otherness of the others. It fails however to highlight the similarities between immigration and integration policies of the two countries as well as the increasing convergence that has been taking place since the 1980s. While Sweden mitigated its multiculturalism to promote an integration policy, France departed from its universalistic stance in order to better address the issue of cultural diversity. Hence, differences between the two countries have been dramatically reduced despite some enduring peculiarities. This investigation hence aims at paving the way for future fruitful comparisons between policies related to otherness in the two countries.